Brain : the complete mind : how it develops, how it works, and how to keep it sharp - Sweeney, Michael S. (Washington, D.C. : National Geographic, 2009)
An illustrated guide to the brain's development and functions. Presents accessible coverage of how the brain works and the latest scientific discoveries, sharing lifestyle tips on how to promote brain health through exercise, nutrition, and specific bolstering activities.
The amazing brain -- The nervous system -- Brain development -- The senses -- Motion -- States of mind -- The feeling brain -- Learning & memory -- The aging brain -- Future of the brain.
Includes bibliographical references (p. 338) and index.
Keywords: Brain -- Popular works; Neurosciences -- Popular works; Cerebro -- Trabajos populares; Neurociencias -- Trabajos populares